Emotion regulation in multiple sclerosis - Radlak, Bogumila (The University of Edinburgh, 2018)
Introduction: The objective of this thesis was to examine aspects of emotion regulation in Multiple Sclerosis (MS). A systematic review was carried out of studies investigating the prevalence of alexithymia in individuals with MS, and its relationship with anxiety and depression. An empirical study was conducted to explore whether there were differences in emotion regulation abilities in individuals with different variants of MS, compared to healthy individuals. Methods: Twelve journal articles were identified via systematic search utilising predefined criteria. Seventy nine individuals with relapsing-remitting type of MS, and 38 individuals with chronic progressive type of MS were recruited to the empirical study. Participants filled in self-report questionnaires measuring difficulties in emotion regulation, illness severity, illness representations and quality of life. Also, 55 healthy volunteers took part in the current study. Results: The estimate of prevalence of alexithymia in MS was approximately twice as high as in general population. Positive relationships between alexithymia and/or anxiety and depressive symptoms were found. Those with MS reported difficulties accepting emotional distress which, to some extent, were predicted by strong illness identity and negative emotional responses to having MS. These findings were independently of illness severity, and type of MS. Perceptions of negative consequences of MS were the only partial mediator of the relationship between illness severity and quality of life. Conclusions: Larger and more representative samples are needed to clarify the impact of alexithymia on the clinical presentations of patients with MS. Psychological interventions targeting non-acceptance of emotional distress and negative illness perceptions are warranted to support those with MS.
Keywords: multiple sclerosis; emotion regulation; alexithymia